Responsible investing in South Africa: Drivers, barriers and enablers - S. Viviers; N. S. Eccles; D. De Jongh; J. K. Bosch; E. V.D.M. Smit; A. Buijs (South African Journal of Business Management, 2008)
Given growing interest in the phenomenon of responsible investing (RI) in South Africa, this study set out to identify and empirically evaluate the most pertinent drivers, barriers and enablers of RI locally. Telephone interviews were conducted with a sample of pension funds, asset managers and advisory service providers during 2007. All three groups of respondents viewed fiduciary responsibility as one of the most important barriers to RI in South Africa. More legislation/regulation and evidence for increased risk-adjusted returns from local RIs were identified as key drivers of RI in South Africa, whereas the two most important enablers were seen as mainstream RI benchmarks and co-operative initiatives.
Keywords: 650